The effect of culture medium of Interfillum terricola (J.B.Petersen) Mikhailyuk et al. (Charophyta) on allelopathic, microbiological, agrophysical and agrochemical characteristics of soil - Tsarenko, P.M.; Zaimenko, N.V.; Didyk, N.P.; Ellanska, N.E.; Pavlyuchenko, N.A.; Ivanytska, B.O.; Yunosheva, O.P.; Demchenko, E.M. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2021)
The influence of the cultural medium of the charophyte Interfillum terricola on the allelopathic, microbiological, agrophysical and agrochemical properties of the soil have been studied in model pot experiments. Allelopathic soil regime was assessed by biological testing methods for water-soluble compounds and direct biotesting, as well as by vital indicators of plants-phytometers of winter wheat (Triticum aestivum L., variety "Smuglyanka") and fodder corn (Zea mays L., variety "Kadr 267 MB"). The seeds were sown immediately after the introduction of the culture fluid. The number of germinated seeds was recorded from the 2nd to the 8th day after sowing. The vital condition of phytometer plants was evaluated at the end of the experiments by morphometric indicators of growth (leaf surface area, dry matter biomass of aboveground parts and roots) and the content of photosynthetic pigments in the leaves. When the experiment was completed, soil samples were taken to determine the cytostatic effect of water-soluble compounds and to carry out microbiological and biochemical analyzes. Phenolic compounds were isolated from the soil by ion exchange (desorption) using an ion exchanger KU-2-8 (Н+). In parallel, the electrical conductivity, redox potential, pH and content of nutrients in the soil were determined. The stimulating effect of cultural medium on seed germination, growth and development of assimilation organs of wheat and corn plants has been revealed. The strength of the effect did not depend on the concentration of growing medium, which is characteristic of signal allelopathically active substances. Allelopathic and cytostatic activity of the soil decreased with the use of Interfillum terricola growing medium. The introduction of the cultural fluid significantly affected the number of microorganisms of different ecological and trophic groups. The lowest number of microorganisms was observed at the minimum rate of introduction of microalga medium, and its increase contributed to the growth of the number of almost all studied groups of microorganisms, indicators of transformation and mineralization of organic matter. Under the influence of the cultural medium, the content of phenolic compounds in the soil decreased by 1.1–1.6 times, especially at the norm of 10 mL. The soil treated with cultural fluid had higher rates of transformation and mineralization of organic matter than untreated. The concentration of phenolic compounds in the soil decreased, apparently, due to the activation of the microbiota resulting in the intensification of the destruction processes. An increase in the electrical conductivity of the soil with the introduction of microalgae inoculum was recorded, which may indicate the release of metal ions into the substrate. This confirms the increase in Ca and Mg.